Propuesta para la implementación de un sistema de gestión de la Inocuidad de los alimentos según la NTC ISO 22000:2018 en la línea de galletería de la Empresa Panadería Arenas C.A. - Garrido Montenegro, Mauricio Santiago (2023)
This work was carried out in a biscuit product production plant located in Quito; The organization has certification in Good Manufacturing Practices, a matrix of Hazard Analysis and Critical Control Points, and external audits. The implementation proposal seeks to find the operational and documentation deficiencies with respect to the control sections of the NTC ISO 22000:2018, for which a diagnostic process was carried out based on the application of Checklists, obtaining the following results: in Chapter 4, Quality Management Systems, 66.67% compliance was obtained; in Chapter 5, Management Responsibility, 58.73%; in Chapter 6, Resource Management, 91.67%; in Chapter 7, Planning and Implementation of Safe Products, 89.83%, and in Chapter 8, Validation, Verification and Improvement of the Management System, 89.80%. The sections with a record of non-compliance allowed the identification of opportunities for improvement in the system that included: an update of the food safety policy, the formation and appointment of a food safety team, the planning of follow-up meetings and improvement of the system with senior management, the implementation of documentation in a single HACCP plan and the updating of management system records. This document details the actions aimed at improving the production processes of the biscuit line, with the aim of achieving a future certification process in NTC ISO 22000:2018.